Kalendarz Polityczny Wileński księdza Franciszka Paprockiego - Jakubėnas, Regina (Slavistica Vilnensis, 2012)
W Wilnie w połowie lat 30. XVIII wieku jezuita ks. Jan Antoni Poszakowski (1684–1757) wydał pierwszy kalendarz, który zapoczątkował nową serię druków w Wielkim Księstwie Litewskim. Druki te stały się jedną z najpoczytniejszych form czytelnictwa w XVIII wieku w WKL1. W 2 połowie XVIII wieku wydawanie jezuickich kalendarzy w Wilnie odnowił historyk ks. Franciszek Paprocki (1723–1805). ... Regina Jakubėnas The Political Vilnius Calendar of the priest Franciszek Paprocki The article is devoted to the publishing of calendars – a permanent publishing initiative, launched in the first half of the 18th century and continued by the Jesuit priest Franciszek Paprocki (1723–1805) in the University Printing House in the second half of the 18th century. Calendars were among the most widely read publications of those times. Kalendarz Polityczny Wileński (the Political Vilnius Calendar), which was being published for more than 25 years, is presented here. It was regularly advertised in the Vilnius press. News about scientific, geographical and astronomical discoveries, statistical data, information about the socio-political system of the European countries, its rulers, the structure of authorities, constitutions, regulations, the decisions of the Parliament, as well as curiosities, pieces of practical advice and gossip were published in the calendar. The calendar became a valuable source of knowledge which reflected cultural changes on the territory of the Great Duchy of Lithuania in the Age of Enlightenment. Keywords: Franciszek Paprocki, calendars of the 18th century, Kalendarz Polityczny Wileński, Great Duchy of Lithuania.